Embryological Characteristics of Human Oocytes With Agar-Like Zona Pellucida and Its Clinical Treatment Strategy - Yang, Dandan; Yang, Han; Yang, Bo; Wang, Kaijuan; Zhu, Qi; Wang, Jing; Ding, Fangfang; Rao, Bihua; Xue, Rufeng; Peng, Jing; Wang, Qiushuang; Cao, Yunxia; et al. (Frontiers in Endocrinology, 2022)
Zona pellucida (ZP) abnormalities are the cause of low fertility or infertility, agar-like ZP is more common in abnormal ZP. The purpose of this exploration is to systematically analyze the fertilization competence of agar-like ZP oocytes, the development characteristics of subsequent embryos as well as the results of embryo transfer, aiming to explore effective clinical treatment strategies. A total of 58 patients with agar-like ZP were set as the case group and the control group involved 3866 patients, in which the patients’ oocytes presented normal ZP. BMI, basal hormone levels, and hormone levels were similar in both groups. The case patients suffered significantly longer infertility years than control (p<0.05), and most patients were diagnosed with pelvic inflammatory diseases. A distinct difference was observed in the structure of oocyte corona cumulus complexes between the two groups. The embryo development parameters, which include the rates of cleavage, high-quality embryo, blastocyst, and high-quality blastocyst in the case group was greatly lower than that in the control group (p<0.01). The rates of cumulative clinical pregnancy and live birth were comparable between the two groups. In the subsequent follow-up, thirty-four of the 58 patients receiving intracytoplasmic single sperm injection (ICSI) or early rescue ICSI (R-ICSI) treatment successfully gave birth to babies, and all of the newborns were with no neonatal defects. In addition, the fertilization rate of the R-ICSI group was significantly lower than that of the ICSI group (p<0.05). The occurrence of agar-like ZP impairs the development competence of human oocytes, however, the human oocytes with agar-like ZP can develop into healthy offspring, and an ICSI regimen is the optimal treatment strategy for them.